Pedagogical Partnership as a Factor of Enrichment of Physical Culture of Junior Schoolchildren by Innovative Technologies: Array - Kornienko, Sergey (Journal of Danubian Studies and Research, 2020)
The article reveals the features of pedagogical school for parents in primary school as an innovative form of pedagogical education of parents to ensure that they acquire the necessary and sufficient knowledge, skills and abilities to lead a healthy lifestyle in the family. The topics are substantiated and the forms of conducting classes in each class of primary school are proposed, which have been successfully tested for ten years in the secondary school of I-III grades № 17 of the city of Ternopil.